Comparative study on thermal comfort between Malay traditional house and modern bungalow house in Perak / Wan Mohamad Adam Wan Namat and Intan Bayani Zakaria - Wan Namat, Wan Mohamad Adam; Zakaria, Intan Bayani (2019)
In this era modernization and urbanization, are exposed by modern building and construction. Thermal comfort is a great influence on health and satisfaction of occupants in indoors living. Thermal comfort is defined as the state of mind that expresses satisfaction with the surrounding environment. Malaysia is a tropical country characterized as warm and humid every year. In most of the survey study, most people spend 80 percent of their lives indoor especially in home. This study examines the level of the thermal comfort in Malay traditional house and modern bungalow house in Malaysia. This study proceeds to analyze the detailed field data collected, with a view to identify the good thermal comfort between these houses. The case study of two Malay traditional houses in this research are located in Batu 14 ¾ Kampung Telok Bekong, Bota, whereas the modern bungalow houses are located Seri Iskandar Perak.